How Involved Do Patients Want to Be in the Medical Decision-Making at the Initial Urogynecology Clinic Visit?. Issue 3 (March 2022) - Westbay, Lauren C.; Adams, William; Barnes, Hayley C.; Gevelinger, Matthew; McKee, Daryl; Fitzgerald, Colleen M.; Acevedo-Alvarez, Marian; Mueller, Elizabeth R.; Pham, Thythy T.
Abstract : Objective: The aim of this study was to compare patients' preferred role in medical decision-making before the initial urogynecology visit to their perceived role after the visit. Methods: This prospective cohort study enrolled women presenting for their initial urogynecology visit. Before and after the visit, patients completed the Control Preference Scale (CPS), which categorizes the role that patients want to have in medical decision-making: active, collaborative, or passive. Patients also completed the Pelvic Floor Distress Inventory, CollaboRATE, Patient Global Impression of Improvement, patient satisfaction, and Short Test of Functional Health Literacy in Adults questionnaires. Univariable and multivariable generalized estimating equations were used. Results: Women (n = 100) with a mean age of 59.1 years (SD = 15.5) participated in the study. Based on CPS before the visit, 50% of the women preferred active involvement, whereas 45% preferred collaborative and 5% preferred passive involvement. After the visit, these rates change to 40%, 48%, and 11%, respectively. On univariable analysis, women were 1.56 times more likely to report a collaborative or passive CPS response after the visit ( P = 0.02). This remained true on multivariable analysis (odds ratio, 1.57; P = 0.04). Patients' CPS responses were not associated with their responses on CollaboRATE, Patient Global Impression of Improvement, patient satisfaction, or Short Test of Functional Health Literacy in Adults. Eighty-eight percent of women reported a fully collaborative visit based on CollaboRATE, and 87% reported being "completely satisfied" with the visit. Conclusions: Despite a change in women's reported involvement in decision-making after their first urogynecology visit compared with their preferences before the visit, most women perceived collaboration during their visit and were completely satisfied.